(untitled) (The Research of Medical Science Review, 2025)
Background: Childbirth is a profound journey influenced by cultural, social, and medical elements. The decision between a C-section and vaginal delivery is crucial for expectant mothers, driven by personal choices, beliefs, and medical guidance. This choice deeply affects the health of the mother, the well-being of the newborn, and the overall childbirth experience. Objective: To investigate the psychosocial and emotional determinants that shape women’s choices between cesarean section and normal delivery in Pakistan. Methodology: This cross-sectional study at Fauji Foundation Hospital, Rawalpindi (May-Oct 2024), surveyed 300 pregnant/postpartum women using questionnaires. It explored factors influencing delivery decisions, analyzing demographics, education, occupation, marital status, family size, insurance, emotional states, social/personal factors, birth history, healthcare/societal influences, and post-birth reflections using descriptive statistics in SPSS (v. 27.0). Results: The study of 300 women, mostly college-educated (41.8%) and married (95.3%), revealed that healthcare provider recommendations (31.6%), fear of pain (8.6%), and personal preference (15.9%) were key in delivery decisions. Most (77.7%) felt informed and influenced by providers (38.9%). High rates of stress (18.9%) and anxiety (80.7%) were noted, alongside the impact of societal expectations (48.8%) and emotional well-being concerns (74.4%). Social support (71.4%), cultural influences (52.2%), preference for natural birth (61.1%), and risk concerns (71.8%) were important. Previous births (64.1%), provider input (64.2%), and societal norms (55.1%) also mattered. Post-birth, 26.0% were very satisfied, and 43.3% reported a positive childbirth experience. Conclusion: Childbirth decisions are shaped by emotional factors (anxiety, stress) and social influences (provider advice, societal norms). Culturally sensitive support is crucial for informed choices prioritizing women's well-being in Rawalpindi-Punjab